Mitsubishi Fusos Car Marketing Strategy in Increasing Sales at PT. Bumen Redja Abadi Latumenten Jakarta - Na, Mung (Riwayat: Educational Journal of History and Humanities, 2023)
This type of research is qualitative research, meaning that the data collected comes from interviews, direct observation, field notes, personal documents, memo notes, and other official documents. This study aims to determine the marketing strategy for Fuso Cars at PT. Bumen Redja Abadi Latumenten Jakarta. The research objective is to find out how to increase Mitsubishi Fuso car sales at PT. Bumen Redja Abadi Latumenten Jakarta. The theory used by researchers is management theory and marketing theory. The research method used is qualitative, meaning that the data collected comes from interviews, direct observation, field notes, personal documents, memo notes, and other official documents. The research obtained shows that PT. Bumen Redja Abadi Latumenten Jakarta carried out a marketing strategy for Mitsubishi Fuso cars through its sales activities by marketing commercial cars (freight transport). The conclusion from the results of research conducted to increase sales at PT. Bumen Redja Abadi Latumenten Jakarta is the best service for customers, and loyal consumers if penetration is carried out on target.